The business of sports : a primer for journalists - Conrad, Mark, 1958- (Routledge communication series., 2011)
This book explores the business aspect of sports with an orientation to those topics that are most relevant to journalists, providing the foundation for understanding the various parts of the sports business. Moving beyond sports writing, this text offers a distinct perspective on professional, college, and international sports organizations - structure, governance, labor issues, and other business factors within the sports community. Written clearly and compellingly, The Business of Sports includes cases (historical, current, and hypothetical) to illustrate how business concerns p.